2018
DOI: 10.1097/md.0000000000011364
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative injection of carbon nanoparticles is beneficial to the patients with thyroid papillary carcinoma

Abstract: Background:More surgeons had noticed the importance of carbon nanoparticles (CNs) in protection of parathyroid grand in the surgery of thyroidectomy and central lymph lode dissection, but paid less attention to the injection time. The purpose of this study was to investigate whether preoperative injection of CNs can improve the dissection of lymph nodes (LNs) and protect parathyroid grand (PG) for the patients with papillary thyroid carcinoma (TC).Methods:A total of 102 consecutive patients were enrolled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…However, inappropriate intraoperative injection of CNs can cause extravasation of CNs around the thyroid gland, making the identification of parathyroid glands and recurrent laryngeal nerve (RLN) challenging (18). Additionally, the intraoperative injection procedure of CNs prolonged the operative time (18)(19)(20). Moreover, the staining rate of the lymph node was not satisfactory (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…However, inappropriate intraoperative injection of CNs can cause extravasation of CNs around the thyroid gland, making the identification of parathyroid glands and recurrent laryngeal nerve (RLN) challenging (18). Additionally, the intraoperative injection procedure of CNs prolonged the operative time (18)(19)(20). Moreover, the staining rate of the lymph node was not satisfactory (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanoparticles with an average diameter of 150nm can enter lymphatic vessels (with an average diameter of 500nm) rather than capillaries (with an average diameter of 30-50nm), allowing the development of lymph nodes. Since the lymphatic vessels of thyroid gland and parathyroid gland do not communicate with each other, most scholars believe that negative development of parathyroid gland has a protective effect on it, and it has been widely used in thyroid cancer surgery in recent years 9 .The results of this study showed that there was a signi cant statistical difference between the experimental group and the control group in the total number of lymph nodes cleared and the positive rate of metastatic lymph nodes. Consistent with the views of luo wenzheng and other researchers [10][11][12] 11111111111156456466---][i]222115415,Considering carbon nanoparticles can help surgeons better identify lymph nodes in the central region, especially the microscopic nodes that are di cult to be distinguished by the naked eye, reduce lymph node residues, and make it easier and more accurate for pathologists to extract lymph nodes 13 .Together, the two can increase the number of lymph nodes detected, and the corresponding seizure rate of metastatic lymph nodes is also improved, which is conducive to more accurate postoperative judgment of staging and prognosis, as well as elimination of potential sources of lymph node recurrence [14][15] .However, there was no statistical difference in the changes of blood calcium and PTH between the experimental group and the control group at 3 and 30 days after surgery (P > 0.…”
Section: Discussmentioning
confidence: 64%
“…We had to emphasize the importance of PG transplantation as soon as possible, especially in the patents that the PG was not in situ or misresection [23]. with the help of new ways of nding RLN, PG recognition and auto-transplantation [24][25][26], BCND may be safe in the patients with cN0 PTC in our study based on the long-term results because it may guarantee an adequate surgical resection in patients with occult nodal disease and reduced the risk of tumor recurrence theoretically. So BCND may be a feasible treatment option, but who was suitable for BCND will be a question to be discussed.…”
Section: Discussionmentioning
confidence: 99%